Contemporary antibiofouling modifications of reverse osmosis desalination membrane: A review - Nidal Hilal (Desalination, 2019)
Biofouling is a persistent and unmet challenge in reverse osmosis (RO) technology. The attachment of microorganisms on the membrane surface has severely deteriorated the performance of RO membranes hence significantly affected the overall productivity and energy consumption of the system. Different strategies have been established to mitigate the thorny issue in order to minimize the adverse impacts of biofouling. This contribution provides a comprehensive review on the contemporary strategies that are focused on RO membrane design and modification to address the biofouling issues. The strategies for the development of anti-biofouling RO membrane in terms of material characteristics and selections as well as the techniques established to render anti-biofouling properties are extensively discussed. The performance of RO membranes through approaches including coating, layer by layer, grafting immobilization and surface patterning are reviewed. Finally, this review is wrapped up with the technological issues and challenges as well as the future perspective of these strategies.